Digital Economy in Tourism and Hospitality Industry - MAMBETOVA, Sagynysh; AYAGANOVA, Meiramgul; KALYKOV, Abay; AKHMETOVA, Assel; YESKEROVA, Zamira (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2021)
Modernization of traditional industries and services, the organization of trade and procurement procedures, related financial and logistics operations, changes in consumption patterns against the background of the penetration of information technologies and the digitization of economic processes create the basis for the formation of new markets and conditions, as well as new approaches to analytics, forecasting and management decisions. Digital platforms are beginning to be used as primary channels for customer interaction and transactions, as well as a means of creating innovative business models, including in the travel industry. The aim of the study is to analyze the digital economy in the tourism and hospitality industry based on the study of foreign experience in the context of the rapid development of the digital economy. The scientific novelty of the research lies in the substantiation of a systematic approach to the development of information technologies in the tourism industry, based on the challenges and risks of the digital economy.